Five-week, low-intensity blood flow restriction rowing improves VO2max in elite rowers - Held, S.; Rappelt, L.; Rein, R.; Deutsch, J.-P.; Wiedenmann, T.; Donath, L. (The Journal of Strength and Conditioning Research, 2024)
This controlled intervention study examined the effects of low-intensity rowing with blood flow restriction (BFR) on maximal oxygen uptake (Vo2max), peak power output during ramp testing (PPO), and 2000-m time trial performance (P2k). Eleven, highly elite, male rowers (22.1 ± 1.6 years; 92.6 ± 3.8 kg; 1.93 ± 0.04 m; 7.9. ± 2.2 years rowing experience; 20.4 ± 2.0 h·w-1 training volume; 11.9 ± 1.1 session per week) trained 5 weeks without BFR (Base) followed by a 5-week BFR intervention period. BFR of the lower limb was applied through customized elastic wraps. BFR took place 3 times a week (accumulated net pBFR: 60 min·wk-1; occlusion per session: 2 times 10 min·session-1) and was used exclusively at low intensities (<2 mmol·L-1). Vo2max, PPO, and P2k were examined before, between, and after both intervention periods. Bayesian`s credible intervals revealed relevantly increased Vo2max +0.30 L·min-1 (95% credible interval: +0.00 to +0.61 L·min-1) adaptations through BFR. By contrast, PPO +14 W (-6 to +34 W) and P2k -5 W (-14 to +3 W) were not noticeably affected by the BFR intervention. This study revealed that 15 sessions of BFR application with a cumulative total BFR load of 5 h over a 5-week macrocycle increased Vo2max remarkably. Thus, pBFR might serve as a promising tool to improve aerobic capacity in highly trained elite rowers.